The Impact of Variable Pricing, Dynamic Pricing, and Sponsored Secondary Markets in Major League Baseball. (February 2020) - Courty, Pascal; Davey, Luke
Toward the end of the 1990s and into the 2000s, Major League Baseball teams moved away from fixed ticket prices, to first setting prices according to expected game demand, and subsequently to dynamically changing prices in response to demand. Teams have also collaborated with secondary ticket marketplaces to sponsor resale. By exploiting a team panel covering seasons 1999-2017, we use fixed effect models to estimate the impact of these pricing innovations on team revenue and team value. Variable pricing increases revenue and team value by 4.2% and 9.5%, respectively. The introduction of dynamic pricing and sponsored secondary markets has no statistically significant effect on revenue or team value.